Clinical characteristics of hereditary hemorrhagic telangiectasia – case series and review of the literature - Popović, Dragan; Sokić-Milutinović, Aleksandrac; Djuranović, Srđan; Alempijević, Tamara; Zgradić, Sanja; Matović, Vera; Tončev, Ljubiša; Lukić, Snežana (Vojnosanitetski pregled, 2021)
Introduction. Hereditary hemorrhagic telangiectasia (HHT) is a rare autosomal dominant disorder with estimated prevalence of one in 5,000 to 10,000. The disease has age-related penetrance and the HHT signs and symptoms occur and worsen with age. A diagnosis of HHT is based on the Curacao`s criteria. Case report. We report a case series of 6 patients diagnosed with HHT, 5 with definite and one with probable diagnosis according to the Curacao criteria. In 5 patients, the recurrent epistaxis occurred in adolescence as the first presentation while one patient presented with melena. The diagnosis was delayed in 5 patients and the presence of HHT was diagnosed during or after the fifth decade. In 4 patients, the overt gastrointestinal bleeding occurred in the later course of the disease. The asymptomatic pulmonary circulation arteriovenous malformations were detected in 2 patients. The cerebral arteriovenous malformations were not detected. Conclusion. Hereditary hemorrhagic telangiectasia is a rare disorder affecting multiple organs. It should be considered in the adolescents with recurrent epistaxis and in the differential diagnosis of anemia with signs of the gastrointestinal bleeding in order to shorten the delay in the diagnosis and subsequently improve the outcome of the disease.